OUTCOME ASSESSMENT OF INTRAVENOUS IMMUNOGLOBULIN THERAPY AS AN ADJUVANT IN TREATMENT OF NEONATAL SEPSIS, A PROSPECTIVE OBSERVATIONAL STUDY - LAVAKUMAR S; MANIMEKALAI K; KARTHIKEYAN K (International Journal of Pharma and Bio Sciences, 2015)
Despite effective antibiotics treatment, mortality due to neonatal sepsis remains high. Immunomodulatory therapy like intravenous immunoglobulin (IV Ig) has been used as an adjunct in an effort to decrease mortality from neonatal sepsis, as newborn infants, particularly those who are preterm and are deficient in IgG. The objective of this study was to assess the outcome of intravenous immunoglobulin therapy as an adjuvant in the treatment of neonatal sepsis. A total of 42 babies who were given IV Ig as an adjuvant along with antibiotics for proven neonatal sepsis formed the potential subjects. Clinical and hematological parameters were assessed following IV Ig administration. The total duration of Neonatal intensive care unit stay was noted. The source, dose, frequency and adverse effects, if any of IV Ig were noted. In our study, both male and female babies were equally affected. More than 90% of the babies were preterm and all the babies had low birth weight. The source of IV Ig was IgG, obtained from pooled human plasma. It was given at the dose of 0.5-0.9 g/kg. No adverse reaction following IV Ig was noted. Following IV Ig administration as an adjuvant in treatment of neonatal sepsis, the improvement in clinical and hematological parameters were better and quicker. The average duration of hospitalization was 6-8 days when IV Ig was given as an adjuvant. Thus duration of NICU stay was less when compared to being treated with antibiotics alone. Hence to conclude, IV Ig as an adjuvant along with antibiotics is a better strategy for both prophylactic as well as treatment of proven neonatal sepsis.